If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -2(x + -1) = 4(x + 4) Reorder the terms: 3(4 + x) + -2(x + -1) = 4(x + 4) (4 * 3 + x * 3) + -2(x + -1) = 4(x + 4) (12 + 3x) + -2(x + -1) = 4(x + 4) Reorder the terms: 12 + 3x + -2(-1 + x) = 4(x + 4) 12 + 3x + (-1 * -2 + x * -2) = 4(x + 4) 12 + 3x + (2 + -2x) = 4(x + 4) Reorder the terms: 12 + 2 + 3x + -2x = 4(x + 4) Combine like terms: 12 + 2 = 14 14 + 3x + -2x = 4(x + 4) Combine like terms: 3x + -2x = 1x 14 + 1x = 4(x + 4) Reorder the terms: 14 + 1x = 4(4 + x) 14 + 1x = (4 * 4 + x * 4) 14 + 1x = (16 + 4x) Solving 14 + 1x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 14 + 1x + -4x = 16 + 4x + -4x Combine like terms: 1x + -4x = -3x 14 + -3x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 14 + -3x = 16 + 0 14 + -3x = 16 Add '-14' to each side of the equation. 14 + -14 + -3x = 16 + -14 Combine like terms: 14 + -14 = 0 0 + -3x = 16 + -14 -3x = 16 + -14 Combine like terms: 16 + -14 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667
| 75-3n+6n=12+15n-2+3n+20 | | -5+3m=3-m | | -3(-2)+6+-2= | | -1+3(x-1)=8x-5(x-2)-14 | | 7x-40-27x=10x+6+36 | | x^2+18x+53=594 | | x^2-5x-11x=0 | | 9x-7=4x+1 | | 9d-4=49 | | 30x=-480 | | x+x*.05=1065.64 | | x+x*.05=1000 | | 3x-17=-14 | | x-16=-30 | | 25w^2-10w+1=0 | | 7-p=3+3p | | 8t-6(-2+7t)=9+t-11 | | X+(X*0.05)=1000 | | 4(5)x-2(3)y=13 | | x^2-2x-6= | | 3y+2y-5=15+y | | X+22=84 | | 10p-6=(-36) | | 2-3(r-7)-7r=4(r-2)+8 | | 6.2g-1.7=1.6g+16.7 | | 13x+2(-15)=43 | | 7x+8=3x+6 | | n^2-18= | | n^2-16= | | 4(y-1)-2(y+1)=4y-(y+5) | | 3x^4-34x^2+63=0 | | y=5x^2-8x-6 |